Healthcare resource use and direct costs in severe aplastic anemia (SAA) patients before and after treatment with eltrombopag. (3rd March 2020) - Cai, Beilei; Said, Qayyim; Li, Xin; Li, Frank (Yunfeng); Arcona, Steve
Abstract: Purpose: This study evaluated healthcare resource utilization (HCRU), and direct costs among severe aplastic anemia (SAA) patients treated with eltrombopag (EPAG) using US claims data. Methods: This retrospective, real-world claims database study identified SAA patients aged ≥2 years treated with EPAG who initiated any SAA treatment between 1 July 2014 and 31 December 2017 (identification period) using the Truven MarketScan databases. A subset of 82 patients treated with EPAG during the identification period were evaluated for all-cause and SAA-related HCRU and direct costs as well as blood transfusion 1 month before EPAG initiation (baseline) and at Month 6 after EPAG initiation (follow-up period). Results: The average patient age was 50.8 ( SD = 20.6) years old, predominantly female ( n = 43, 52.4%), and had a mean CCI at baseline of 1.1 ( SD = 1.7). Hospitalizations, and ER, office, and outpatient visits were significantly lower at Month 6 after EPAG initiation compared with 1 month before EPAG initiation ( p < .05 for all four all-cause HCRU and SAA-related hospitalizations). An almost two-fold decrease in reliance on biweekly blood transfusions was observed: 1.0 at weeks 1–2 to 0.5 at Month 6 after EPAG initiation. Although prescription costs (mean [ SD ]) were significantly higher at Month 6 after EPAG initiation compared with 1 month before EPAG initiation (difference of 11, 045 USD [ SD = 18, 801]), these increases were offset by savings in direct costs. Overall, a mean reduction in total all-cause costs of 29, 391 USD [ SD = 137, 770] was reported at Month 6 after EPAG initiation due to substantial reductions in hospitalization (40, 060 USD [ SD = 123, 198]) and outpatient visits (2, 043 USD [ SD = 25, 264]). Conclusion: All-cause and SAA-related HCRU were reduced following EPAG treatment. Prescription costs were higher following treatment; however, these costs were generally offset by reductions in direct costs. These results provide real-world evidence around the role of EPAG in SAA treatment.